Interactive impact of ethnic distance and cultural familiarity on the perceived effects of free trade agreements - Kingshott, R.; Sharma, P.; Hosie, P.; Davcik, N. (Asia Pacific Journal of Management, 2019)
Past research on free trade agreements (FTAs) mostly uses an economic perspective to assess their impact on the level of trade and investments between nations. As a result, there is a distinct paucity of research on the perceptions of employees and managers in organizations affected by FTAs, towards the likely outcomes of those FTAs. We address this gap by using the context of recently signed China-Australia free trade agreement (ChAFTA) to develop a multidimensional scale for the perceived advantages and disadvantages of FTAs. Drawing on social identity theory and the similarly-attraction paradigm we also show direct and interactive effects of perceived ethnic distance (between home and partner country) and cultural familiarity (with the FTA partner country) on these perceived outcomes of FTAs. Our findings highlight the need to look beyond the economic perspective and consider a much broader range of perceived outcomes of FTAs